Comparative Genome Analysis of Three Komagataeibacter Strains Used for Practical Production of Nata-de-Coco - Ishiya, Koji; Kosaka, Hideki; Inaoka, Takashi; Kimura, Keitarou; Nakashima, Nobutaka (Frontiers in Microbiology, 2022)
We determined the whole genome sequences of three bacterial strains, designated as FNDCR1, FNDCF1, and FNDCR2, isolated from a practical nata-de-coco producing bacterial culture. Only FNDCR1 and FNDCR2 strains had the ability to produce cellulose. The 16S rDNA sequence and phylogenetic analysis revealed that all strains belonged to the Komagataeibacter genus but belonged to a different clade within the genus. Comparative genomic analysis revealed cross-strain distribution of duplicated sequences in Komagataeibacter genomes. It is particularly interesting that FNDCR1 has many duplicated sequences within the genome independently of the phylogenetic clade, suggesting that these duplications might have been obtained specifically for this strain. Analysis of the cellulose biosynthesis operon of the three determined strain genomes indicated that several cellulose synthesis-related genes, which are present in FNDCR1 and FNDCR2, were lost in the FNDCF1 strain. These findings reveal important genetic insights into practical nata de coco-producing bacteria that can be used in food development. Furthermore, our results also shed light on the variation in their cellulose-producing abilities and illustrate why genetic traits are unstable for Komagataeibacter and Komagataeibacter-related acetic acid bacteria.